Policing Victims and Perpetrators of Intimate Partner Violence in Jamaica - Cush Sewell Lewis; Stacey-Ann Wilson (International Journal for Crime, Justice and Social Democracy)
Intimate partner violence (IPV) presents various challenges for victims and the police tasked with protecting them and investigating perpetrators. Using a mixed-methods approach, this article highlights some of the main challenges of policing IPV in Jamaica, a small island developing state. We present findings from interviews with police officers and content analysis of key legislation within a broader discussion, incorporating secondary data from national surveys and community focus groups. Collectively, this provides a comprehensive understanding of the challenges of policing IPV. We discuss some of the historical and social factors contributing to IPV in the country and examine how the police balance victim support with the investigation of perpetrators. Additionally, we identify key institutional and legislative barriers, such as inadequate training and legal limitations, which hinder effective policing. Finally, we propose the problem-oriented policing (POP) framework as a potential solution to improve the handling of IPV cases in Jamaica.